PENGARUH ADVERSITY QUOTIONT DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Dian Palupi (Kompetensi (Competence : Journal of Management Studies), 2015)
Entrepreneurial intention among students college still low, this is a challenge for all people including academics. Entrepreneurial education is expected to give positive stimulus to encourage entepreneurial intention among students. The aim of this study is to examine whether Adversity Quotient (AQ), attitude toward entrepreneurship, entrepreneurial education affects entrepreneurial intention. Sample for this research is to students from Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya. The linier regression analysis was used to examine the hypothesis and it was in condition supported. The result shows that attitude toward entrepreneurship influences entrepreneurial intention positively (β:0.342, p kurang dari 0.05), while entrepreneurial education has no significant effect on the entrepreneurial intention. One of the dimensions of Adversity Quotient, controls gave significant effect on entrepreneurial intention (β: 0476, p kurang dari 0.05). This indication shows that attitude toward entrepreneurship is appropriate indicators in order to encourage entepreneurial intention among students, positive attitude in entrepreneurship will increasing entrepreneurial behavior.